Silica-calcium phosphate nanoparticles delivering recombinant influenza hemagglutinin DNA can induce long-lasting T cell immune cross-protection in mice - Liu, Xiaoxi; Wang, Qingyu; Shi, Yuhua; Zhan, Li; Xu, Lipeng; Hui, Jiaru; Xie, Kunpeng; Li, Chenxi; Li, Chunjiang; Su, Weiheng; Cheng, Xianbin; Shan, Yaming (Frontiers in Immunology, 2025)
IntroductionVaccination remains one of the key tools to prevent influenza pandemic. The influenza vaccine induces durable cross-subtype protection through T-cell immunity, demonstrating significant future potential. DNA vaccines are effective in sustaining the expression of antigens, which can trigger T-cell immune responses. Calcium phosphate nanoparticles can also induce T-cell immune responses by assisting in the activation of DC cells by antigens.MethodsThis study developed silica-coated calcium phosphate nanoparticles (226 nm) encapsulating influenza hemagglutinin plasmids (pHAF/pHAG) via polyethyleneimine adsorption. Further analysis of its bioactivity was conducted through experiments.ResultsThe nanoparticles demonstrated excellent stability (PDI<0.3 for 7 days), efficient pDNA encapsulation (confirmed by UV), and sustained release (93.14% ± 4.12% at 72 h). DC2.4 cells uptake assays revealed significant antigen-presenting cell internalization (p<0.0001). BALB/c mice were immunized subcutaneously using a prime-boost-boost regimen at two-week intervals. Splenocyte analysis revealed sustained elevation of CD4+ and CD8+ T cell proportions (p<0.05) at 12 weeks post-immunization, suggesting nanoparticle-induced durable T cell immunity. Post-immunization challenge with heterologous H3N2 revealed striking protection: SCPs/pHAF conferred 100% survival, while SCPs/pHAG achieved 66% survival. Notably, SCPs/pDNA immunization significantly reduced lung viral titers versus controls (p<0.05), demonstrating robust cross-subtype protection against lethal infection.DiscussionThis study establishes a significant conceptual framework for advancing the development of DNA-based influenza vaccines with sustained protective efficacy.